Steel materials
Patent Information
- Application Number
- JP2024536506
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-08-07
- Filing Date
- 2024-03-18
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2044-03-18
AI Technical Summary
【0013】 本開示による鋼材は、125ksi以上(862MPa以上)の高い強度と、優れた低温靭性とを両立できる。
Smart Images

Figure 0007633586000009 
Figure 0007633586000010 
Figure 0007633586000001
Abstract
Description
[Technical field]
[0001] This disclosure relates to steel products, and more particularly, to steel products suitable for use in oil wells. [Background technology]
[0002] As oil wells and gas wells (hereinafter, oil wells and gas wells are collectively referred to simply as "oil wells") become deeper, there is a demand for higher strength steel materials for oil wells, such as steel pipes for oil wells. Specifically, 80 ksi class (yield strength of 80 to less than 95 ksi, i.e., less than 552 to 655 MPa) and 95 ksi class (yield strength of 95 to less than 110 ksi, i.e., less than 655 to 758 MPa) steel materials for oil wells are widely used, and recently, there has been a demand for 110 ksi class (yield strength of 758 to less than 862 MPa) steel materials for oil wells.
[0003] Oil wells may also contain corrosive hydrogen sulfide gas (H2S) and carbon dioxide gas (CO2). Therefore, steel materials expected to be used as oil well steel materials are required to have not only high strength but also excellent corrosion resistance. In addition, steel materials for oil wells are subjected to stress during use. For this reason, sulfide stress cracking resistance (hereinafter referred to as SSC resistance) has been used as an indicator of the excellent corrosion resistance of steel materials for oil wells.
[0004] Techniques for improving the strength and SSC resistance of steel materials have been proposed in JP 2006-28612 A (Patent Document 1), WO 2008 / 123422 A (Patent Document 2), and JP 2017-166060 A (Patent Document 3).
[0005] The steel material disclosed in Patent Document 1 is a steel for steel pipes, and contains, by mass%, C: 0.2-0.7%, Si: 0.01-0.8%, Mn: 0.1-1.5%, S: 0.005% or less, P: 0.03% or less, Al: 0.0005-0.1%, Ti: 0.005-0.05%, Ca: 0.0004-0.005%, N: 0.007% or less, Cr: 0.1-1.5%, Mo: 0.2-1.0%, and the balance being Fe and impurities. This steel material further has a (Ca%) / (Al%) ratio of 0.55-1.72 and a (Ca%) / (Ti%) ratio of 0.7-19 in non-metallic inclusions containing Ca, Al, Ti, N, O, and S. Patent Document 1 states that this steel material has a high yield strength of more than 758 MPa and excellent SSC resistance.
[0006] The steel material disclosed in Patent Document 2 is a low alloy steel containing, by mass%, C: 0.10-0.20%, Si: 0.05-1.0%, Mn: 0.05-1.5%, Cr: 1.0-2.0%, Mo: 0.05-2.0%, Al: 0.10% or less, and Ti: 0.002-0.05%, with Ceq (=C+(Mn / 6)+(Cr+Mo+V) / 5) being 0.65 or more, and the balance being Fe and impurities, among which P: 0.025% or less, S: 0.010% or less, N: 0.007% or less, and B: less than 0.0003%. This steel material further contains M having a grain size of 1 μm or more. 23 C6 type precipitates are 0.1 pieces / mm 2 The steel material has a yield strength of 654 to 793 MPa and is described in Patent Document 2 as having excellent SSC resistance even in a high-pressure hydrogen sulfide environment.
[0007] The steel material disclosed in Patent Document 3 is a material for high-strength steel pipes for oil wells, and consists, in mass%, of C: 0.20 to 0.45%, Si: 0.05 to 0.40%, Mn: 0.3 to 0.9%, P: 0.015% or less, S: 0.005% or less, Al: 0.005 to 0.10%, N: 0.001 to 0.006%, Cr: 0.1 to 0.8%, Mo: 0.1 to 1.6%, V: 0.02 to 0.2%, Nb: 0.001 to 0.04%, B: 0.0003 to 0.0030%, O (oxygen): 0.0030% or less, and the balance being Fe and unavoidable impurities. This steel further has a Rockwell hardness HRC that satisfies the formula (15.6×[%C]+29.2≦HRC<60.5×[%C]+31.1). Patent Document 3 describes that this steel provides a steel pipe having a yield strength of 758 to less than 862 MPa and excellent SSC resistance. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2006-28612 A [Patent Document 2] International Publication No. 2008 / 123422 [Patent Document 3] JP 2017-166060 A Summary of the Invention [Problem to be solved by the invention]
[0009] In recent years, development of deep wells below sea level has also become active. Specifically, oil well steel materials intended for use in so-called deep sea oil fields at depths of 2000 m or more are required to have high strength, for example, of 125 ksi or more (yield strength of 125 ksi or more, i.e., 862 MPa or more). The water temperature in such deep sea oil fields is even lower. Therefore, low temperature toughness is also required for oil well steel materials intended for use in such deep sea oil fields. However, there is a concern that increasing the yield strength of the steel material will result in a decrease in the low temperature toughness of the steel material.
[0010] In other words, oil well steel materials intended for use in such harsh environments are required to have both high strength of 125 ksi or more and excellent low-temperature toughness. On the other hand, Patent Documents 1 to 3 do not consider achieving both high strength of 125 ksi or more and excellent low-temperature toughness.
[0011] An object of the present disclosure is to provide a steel material that combines high strength of 125 ksi or more (862 MPa or more) with excellent low-temperature toughness. [Means for solving the problem]
[0012] The steel material according to the present disclosure is In mass%, C: 0.15-0.45%, Si: 0.05 to 1.00%, Mn: 0.05 to 1.00%, P:0.030% or less, S: 0.0050% or less, Al: 0.005 to 0.100%, Cr: 0.30~1.50%, Mo: 0.20-2.00%, Ti: 0.002 to 0.030%, Nb: 0.002 to 0.100%, B: 0.0005~0.0040%, N: 0.0100% or less, O: 0.0040% or less, V: 0~0.30%, Cu: 0-0.50%, Ni: 0-0.50%, W: 0 to 0.50%, Ca: 0 to 0.0100%, Mg: 0 to 0.0100%, Zr: 0 to 0.0100%, Rare earth elements: 0 to 0.0100%, and the balance being Fe and impurities, The yield strength is 862 to 1034 MPa. In the steel material, The Al content is 20% or more, the O content is 10% or more, and the number density of Al oxides with a major axis of 5.0 μm or more is 30 / 200 mm 2 is less than In mass%, the Al content is less than 20%, the Si content is 20% or more, the O content is 10% or more, and the number density of silicon oxides having a major axis of 5.0 μm or more is 5 pieces / 200 mm 2 The following is the result. Effect of the Invention
[0013] The steel material according to the present disclosure can achieve both high strength of 125 ksi or more (862 MPa or more) and excellent low-temperature toughness. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a diagram showing the relationship between the number density (pieces / 200 mm2) of coarse Si oxides (Si oxides with a major axis of 5.0 μm or more) and the fracture appearance transition temperature (°C), which is an index of low-temperature toughness, for examples having a yield strength of less than 945 MPa among the present examples. [Diagram 2] FIG. 2 is a graph showing the relationship between the number density (pieces / 200 mm2) of coarse Si oxides (Si oxides with a major axis of 5.0 μm or more) and the fracture appearance transition temperature (°C), which is an index of low-temperature toughness, for the examples having a yield strength of 945 MPa or more among the present examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] First, the inventors focused on the chemical composition and investigated how to obtain a steel material that has both a yield strength of 125 ksi or more and excellent low-temperature toughness. As a result, the inventors found that the composition is, by mass%, C: 0.15-0.45%, Si: 0.05-1.00%, Mn: 0.05-1.00%, P: 0.030% or less, S: 0.0050% or less, Al: 0.005-0.100%, Cr: 0.30-1.50%, Mo: 0.20-2.00%, Ti: 0.002-0.030%, Nb: 0.002-0.100%, B: 0.0005-0.0040%, N: 0.0 It was thought that if a steel material with the following composition was used, namely, Cu: 0-0.50%, Ni: 0-0.50%, W: 0-0.50%, Ca: 0-0.0100%, Mg: 0-0.0100%, Zr: 0-0.0100%, rare earth elements: 0-0.0100%, and the balance being Fe and impurities, it would be possible to achieve both a yield strength of 125 ksi or more and excellent low-temperature toughness.
[0016] Next, the inventors of the present invention investigated various methods for improving the low-temperature toughness of a steel material having the above-mentioned chemical composition and a yield strength of 125 ksi or more. Specifically, the inventors of the present invention considered that if coarse oxide-based inclusions could be reduced, it would be possible to improve the low-temperature toughness while maintaining the yield strength. Here, in a steel material having the above-mentioned chemical composition, Al oxides mainly composed of Al2O3 tend to coarsen. Therefore, the inventors of the present invention first focused on the coarse Al oxides.
[0017] As a result of the investigation by the present inventors, in a steel material having the above-mentioned chemical composition and a yield strength of 125 ksi or more, the number density of Al oxide particles having a major axis of 5.0 μm or more is 30 particles / 200 mm 2 It has been revealed that if the content is less than 1.0 μm, low-temperature toughness may be improved. Here, in this specification, particles having an Al content of 20% or more and an O content of 10% or more, in mass%, are also referred to as "Al oxides". Furthermore, in this specification, Al oxides having a major axis of 5.0 μm or more are also referred to as "coarse Al oxides".
[0018] Here, Al oxides are hard oxides and tend to reduce the toughness of the steel material. In particular, when the yield strength is increased to 125 ksi or more, the effect of coarse Al oxides tends to become apparent, and low-temperature toughness tends to decrease significantly. Therefore, in the steel material according to this embodiment having the above-mentioned chemical composition and a yield strength of 125 ksi or more, the number density of coarse Al oxides is set to 30 particles / 200 mm 2 Less than.
[0019] On the other hand, the above-mentioned chemical composition, the number density of coarse Al oxides is 30 pieces / 200 mm 2 In some cases, even if the steel material has a yield strength of 125 ksi or more, it may not be possible to stably obtain excellent low-temperature toughness. Therefore, the inventors have developed a steel material having the above-mentioned chemical composition and a yield strength of 125 ksi or more, and a number density of coarse Al oxides of 30 particles / 200 mm 2 As a result of detailed investigations by the inventors, it was found that a steel material having the above-mentioned chemical composition, a yield strength of 125 ksi or more, and a number density of coarse Al oxides of 30 particles / 200 mm 2 It became clear that in steel materials with a hardness of less than 100%, if not only the coarse Al oxides in the steel but also the coarse Si oxides can be reduced, it may be possible to stably obtain excellent low-temperature toughness.
[0020] In this specification, particles having an Al content of less than 20%, a Si content of 20% or more, and an O content of 10% or more, in mass%, are also referred to as "Si oxides". In this specification, Si oxides having a major axis of 5.0 μm or more are also referred to as "coarse Si oxides". Hereinafter, particles having the above-mentioned chemical composition, a yield strength of 125 ksi or more, and a number density of coarse Al oxides of 30 particles / 200 mm 2 The relationship between coarse Si oxides and low-temperature toughness for steel materials having a hardness of less than 1000 mm will be specifically explained with reference to the drawings.
[0021] FIG. 1 shows the number density (pieces / 200 mm ) of coarse Si oxides (Si oxides with a major axis of 5.0 μm or more) for the examples with a yield strength of less than 945 MPa. 21 is a graph showing the relationship between the fracture appearance transition temperature (°C), which is an index of low-temperature toughness, and the fracture appearance transition temperature (°C), which is an index of low-temperature toughness. 2 The number density (pieces / 200 mm ) of coarse Si oxides was determined by the method described below for steel products with a diameter of less than 1 mm. 2 ) and the fracture appearance transition temperature (℃) obtained by the method described below.
[0022] With reference to FIG. 1, the above-mentioned chemical composition and the yield strength of less than 862 to 945 MPa, and the number density of the coarse Al oxides is 30 / 200 mm 2 In steels with a particle density of less than 5 particles / 200 mm 2 If the fracture surface transition temperature was below -50°C, excellent low-temperature toughness was observed.
[0023] Furthermore, FIG. 2 shows the number density (pieces / 200 mm ) of coarse Si oxides (Si oxides with a major axis of 5.0 μm or more) for the examples with a yield strength of 945 MPa or more among the present examples. 2 2 is a graph showing the relationship between the fracture appearance transition temperature (°C), which is an index of low-temperature toughness, and the fracture appearance transition temperature (°C), which is an index of low-temperature toughness. 2 The number density (pieces / 200 mm ) of coarse Si oxides was determined by the method described below for steel products with a diameter of less than 1 mm. 2 ) and the fracture appearance transition temperature (℃) obtained by the method described below.
[0024] With reference to FIG. 2, the above-mentioned chemical composition and the yield strength of 945 to 1034 MPa, and the number density of the coarse Al oxides is 30 pieces / 200 mm 2 In steels with a particle density of less than 5 particles / 200 mm 2 If the fracture surface transition temperature was below -40°C, excellent low-temperature toughness was observed.
[0025] Therefore, in this embodiment, the above-mentioned chemical composition and the yield strength of 862 to 1034 MPa, and the number density of the coarse Al oxides is 30 pieces / 200 mm 2 The number density of coarse Si oxides is set to less than 5 pieces / 200 mm 2 As a result, the steel material according to this embodiment can achieve both a yield strength of 125 ksi or more and excellent low-temperature toughness.
[0026] The details of why the low-temperature toughness of steel is improved by reducing the number density of coarse Si oxides are not clear. However, the present inventors speculate as follows. When manufacturing steel having the above-mentioned chemical composition, deoxidation is mainly performed with aluminum (Al) in the steelmaking process. Therefore, in steel having the above-mentioned chemical composition, Al oxides represented by Al2O3 have been studied, and Si oxides, which are few in number, have not been paid attention. However, when the yield strength is increased to 125 ksi or more, there is a possibility that a decrease in low-temperature toughness is likely to become apparent not only for coarse Al oxides but also for coarse Si oxides, which are few in number. Therefore, the number density of coarse Al oxides is set to 30 / 200 mm 2 Not only to reduce the number density of coarse silicon oxide particles to less than 5 particles / 200 mm 2 The present inventors speculate that by setting the temperature to below 125 ksi, it may be possible to stably obtain excellent low-temperature toughness even if the steel has a yield strength of 125 ksi or more.
[0027] However, it is possible that the low-temperature toughness of the steel material is increased by a mechanism different from that presumed by the present inventors. 2 For steels with a particle size of less than 100 mm, the particle density of coarse Si oxides is set at 5 particles / 200 mm. 2 It is demonstrated by the examples described later that excellent low-temperature toughness can be obtained by satisfying the following conditions.
[0028] The gist of the steel material according to this embodiment, which was completed based on the above findings, is as follows.
[0029] [1] A steel material, In mass%, C: 0.15-0.45%, Si: 0.05 to 1.00%, Mn: 0.05 to 1.00%, P:0.030% or less, S: 0.0050% or less, Al: 0.005 to 0.100%, Cr: 0.30~1.50%, Mo: 0.20-2.00%, Ti: 0.002 to 0.030%, Nb: 0.002 to 0.100%, B: 0.0005~0.0040%, N: 0.0100% or less, O: 0.0040% or less, V: 0~0.30%, Cu: 0-0.50%, Ni: 0-0.50%, W: 0 to 0.50%, Ca: 0 to 0.0100%, Mg: 0 to 0.0100%, Zr: 0 to 0.0100%, Rare earth elements: 0 to 0.0100%, and the balance being Fe and impurities, The yield strength is 862 to 1034 MPa. In the steel material, The Al content is 20% or more, the O content is 10% or more, and the number density of Al oxides with a major axis of 5.0 μm or more is 30 / 200 mm 2 is less than In mass%, the Al content is less than 20%, the Si content is 20% or more, the O content is 10% or more, and the number density of silicon oxides having a major axis of 5.0 μm or more is 5 pieces / 200 mm 2 Below is the Steel material.
[0030] [2] The steel material according to [1], V: 0.01 to 0.30%, Cu: 0.01 to 0.50%, Ni: 0.01 to 0.50%, W: 0.01 to 0.50%, Ca: 0.0001 to 0.0100%, Mg: 0.0001 to 0.0100%, Zr: 0.0001 to 0.0100%, and Rare earth elements: containing one or more elements selected from the group consisting of 0.0001 to 0.0100%; Steel material.
[0031] [3] The steel material according to [1] or [2], The steel material is a seamless steel pipe. Steel material.
[0032] The shape of the steel material according to this embodiment is not particularly limited. The steel material according to this embodiment may be a steel pipe, a round bar (solid material), or a steel plate. The round bar means a steel bar having a circular cross section perpendicular to the axial direction. The steel pipe may be a seamless steel pipe or a welded steel pipe.
[0033] The steel material according to this embodiment will be described in detail below. "%" for elements means mass % unless otherwise specified.
[0034] [Chemical composition] The chemical composition of the steel material according to this embodiment contains the following elements.
[0035] C: 0.15-0.45% Carbon (C) improves the hardenability of steel material and increases its strength. Furthermore, C promotes spheroidization of carbides during tempering in the manufacturing process, and increases the low-temperature toughness of the steel material. If the C content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the C content is too high, even if the contents of other elements are within the range of this embodiment, the amount of carbides becomes too large, and the low-temperature toughness of the steel material decreases. Therefore, the C content is 0.15 to 0.45%. The preferred lower limit of the C content is 0.18%, more preferably 0.20%, more preferably 0.22%, and more preferably 0.25%. The preferred upper limit of the C content is 0.40%, more preferably 0.38%, more preferably 0.35%, and more preferably 0.30%.
[0036] Silicon: 0.05 to 1.00% Silicon (Si) deoxidizes steel. If the Si content is too low, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Si content is too high, a large number of coarse Si oxides are generated, even if the contents of other elements are within the range of this embodiment, and the low-temperature toughness of the steel material may decrease. Therefore, the Si content is 0.05 to 1.00%. The preferred lower limit of the Si content is 0.10%, more preferably 0.15%, and more preferably 0.20%. The preferred upper limit of the Si content is 0.85%, more preferably 0.75%, more preferably 0.60%, more preferably 0.50%, and more preferably 0.40%.
[0037] Mn: 0.05 to 1.00% Manganese (Mn) deoxidizes steel. Mn also enhances the hardenability of steel. If the Mn content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Mn content is too high, coarse sulfide-based inclusions are generated, and the low-temperature toughness of the steel is reduced, even if the contents of other elements are within the range of this embodiment. Therefore, the Mn content is 0.05 to 1.00%. The preferred lower limit of the Mn content is 0.06%, more preferably 0.08%, and more preferably 0.10%. The preferred upper limit of the Mn content is 0.90%, more preferably 0.80%, more preferably 0.70%, more preferably 0.60%, more preferably 0.50%, and more preferably 0.45%.
[0038] P:0.030% or less Phosphorus (P) is an impurity. That is, the lower limit of the P content is more than 0%. If the P content is too high, even if the contents of other elements are within the range of this embodiment, P will segregate to grain boundaries, and the low-temperature toughness of the steel material will decrease. Therefore, the P content is 0.030% or less. A preferred upper limit of the P content is 0.025%, more preferably 0.020%, more preferably 0.015%, and even more preferably 0.010%. The P content is preferably as low as possible. However, an extreme reduction in the P content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, a preferred lower limit of the P content is 0.001%, more preferably 0.002%, and even more preferably 0.003%.
[0039] S: 0.0050% or less Sulfur (S) is an impurity. That is, the lower limit of the S content is more than 0%. If the S content is too high, even if the contents of other elements are within the range of this embodiment, S will segregate to grain boundaries, and the low-temperature toughness of the steel material will decrease. Therefore, the S content is 0.0050% or less. A preferred upper limit of the S content is 0.0040%, more preferably 0.0030%, more preferably 0.0020%, and even more preferably 0.0015%. The S content is preferably as low as possible. However, an extreme reduction in the S content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, a preferred lower limit of the S content is 0.0001%, more preferably 0.0002%, and even more preferably 0.0003%.
[0040] Al: 0.005 to 0.100% Aluminum (Al) deoxidizes steel. If the Al content is too low, the above effect is not sufficiently obtained even if the contents of other elements are within the range of this embodiment, and the low-temperature toughness of the steel material is reduced. On the other hand, if the Al content is too high, a large number of coarse Al oxides are generated even if the contents of other elements are within the range of this embodiment, and the low-temperature toughness of the steel material is reduced. Therefore, the Al content is 0.005 to 0.100%. The preferred lower limit of the Al content is 0.010%, more preferably 0.015%, and more preferably 0.020%. The preferred upper limit of the Al content is 0.080%, more preferably 0.060%, more preferably 0.040%, and more preferably 0.035%. The "Al" content in this specification means the content of "acid-soluble Al", that is, "sol.Al".
[0041] Cr: 0.30~1.50% Chromium (Cr) enhances the hardenability of steel. Cr also enhances the temper softening resistance of steel, making high-temperature tempering possible. As a result, the low-temperature toughness of the steel is enhanced. If the Cr content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Cr content is too high, the low-temperature toughness of the steel is reduced even if the contents of other elements are within the range of this embodiment. Therefore, the Cr content is 0.30 to 1.50%. The preferred lower limit of the Cr content is 0.35%, more preferably 0.40%, and more preferably 0.50%. The preferred upper limit of the Cr content is 1.40%, more preferably 1.30%, more preferably 1.20%, more preferably 1.10%, and more preferably 1.05%.
[0042] Mo: 0.20~2.00% Molybdenum (Mo) enhances the hardenability of steel. Mo also enhances the temper softening resistance of steel and enables high-temperature tempering. As a result, the low-temperature toughness of steel is enhanced. If the Mo content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Mo content is too high, the above effects are saturated. Therefore, the Mo content is 0.20 to 2.00%. The preferred lower limit of the Mo content is 0.22%, more preferably 0.25%, more preferably 0.30%, more preferably 0.40%, more preferably 0.45%, more preferably 0.50%, and more preferably 0.60%. The preferred upper limit of the Mo content is 1.80%, more preferably 1.60%, more preferably 1.40%, and more preferably 1.30%. In addition, when the yield strength is 945 MPa or more, the lower limit of the Mo content is preferably 0.40%.
[0043] Ti: 0.002~0.030% Titanium (Ti) combines with N to form nitrides, and the pinning effect refines the grains of the steel material. As a result, the strength of the steel material is increased. If the Ti content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Ti content is too high, even if the contents of other elements are within the range of this embodiment, the Ti nitrides become coarse, and the low-temperature toughness of the steel material decreases. Therefore, the Ti content is 0.002 to 0.030%. The preferred lower limit of the Ti content is 0.003%, and more preferably 0.004%. The preferred upper limit of the Ti content is 0.028%, more preferably 0.025%, more preferably 0.023%, more preferably 0.020%, more preferably 0.018%, more preferably 0.015%, more preferably 0.010%, and more preferably 0.008%.
[0044] Nb: 0.002 to 0.100% Niobium (Nb) combines with C and / or N to form carbides, nitrides, or carbonitrides (hereinafter referred to as "carbonitrides, etc."). Carbonitrides, etc., refine the grains of steel by a pinning effect, and improve the low-temperature toughness of the steel. Nb also forms fine carbides during tempering to improve the tempering softening resistance of the steel, thereby improving the strength of the steel. If the Nb content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Nb content is too high, even if the contents of other elements are within the range of this embodiment, excessive carbonitrides, etc. are generated, and the low-temperature toughness of the steel decreases. Therefore, the Nb content is 0.002 to 0.100%. The preferable lower limit of the Nb content is 0.005%, more preferably 0.010%, more preferably 0.015%, more preferably 0.020%, and more preferably 0.025%. The upper limit of the Nb content is preferably 0.080%, more preferably 0.060%, further preferably 0.040%, and further preferably 0.035%.
[0045] B: 0.0005~0.0040% Boron (B) dissolves in steel to improve the hardenability of the steel material and increase the strength of the steel material. If the B content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the B content is too high, coarse nitrides are generated and the low-temperature toughness of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the B content is 0.0005 to 0.0040%. The preferred lower limit of the B content is 0.0006%, more preferably 0.0008%, and more preferably 0.0010%. The preferred upper limit of the B content is 0.0035%, more preferably 0.0030%, more preferably 0.0025%, more preferably 0.0020%, and more preferably 0.0015%.
[0046] N: 0.0100% or less Nitrogen (N) is inevitably contained. That is, the lower limit of the N content is more than 0%. N combines with Ti to form nitrides, and the grains of the steel are refined by the pinning effect. As a result, the strength of the steel is increased. However, if the N content is too high, even if the contents of other elements are within the range of this embodiment, coarse nitrides are formed, and the low-temperature toughness of the steel is reduced. Therefore, the N content is 0.0100% or less. The preferred upper limit of the N content is 0.0080%, more preferably 0.0060%, more preferably 0.0050%, more preferably 0.0045%, and more preferably 0.0040%. The preferred lower limit of the N content for more effectively obtaining the above effects is 0.0005%, more preferably 0.0010%, more preferably 0.0015%, more preferably 0.0020%, more preferably 0.0025%, and more preferably 0.0030%.
[0047] O: 0.0040% or less Oxygen (O) is an impurity. That is, the lower limit of the O content is more than 0%. If the O content is too high, even if the contents of other elements are within the range of this embodiment, coarse oxides are formed, and the low-temperature toughness of the steel material decreases. Therefore, the O content is 0.0040% or less. A preferred upper limit of the O content is 0.0035%, more preferably 0.0030%, more preferably 0.0025%, and even more preferably 0.0020%. The O content is preferably as low as possible. However, an extreme reduction in the O content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, a preferred lower limit of the O content is 0.0001%, more preferably 0.0002%, and even more preferably 0.0003%.
[0048] The balance of the chemical composition of the steel material according to the present embodiment is composed of Fe and impurities. Here, the term "impurities" refers to substances that are mixed in from raw materials such as ore and scrap, or from the manufacturing environment, during industrial production of the steel material, and that are permissible within a range that does not adversely affect the steel material according to the present embodiment.
[0049] [Optional element] The chemical composition of the above-mentioned steel material may further contain V instead of a portion of Fe.
[0050] V: 0~0.30% Vanadium (V) is an optional element and may not be contained. That is, the V content may be 0%. When it is contained, V forms carbonitrides and the like. Carbonitrides and the like refine the grains of the steel material by the pinning effect, and increase the low-temperature toughness of the steel material. V also forms fine carbides during tempering to increase the tempering softening resistance of the steel material and increase the strength of the steel material. If even a small amount of V is contained, the above effects can be obtained to some extent. However, if the V content is too high, even if the contents of other elements are within the range of this embodiment, carbonitrides and the like are excessively generated, and the low-temperature toughness of the steel material decreases. Therefore, the V content is 0 to 0.30%. The preferable lower limit of the V content is more than 0%, more preferably 0.01%, more preferably 0.03%, more preferably 0.05%, and more preferably 0.08%. The preferable upper limit of the V content is 0.25%, more preferably 0.20%, and more preferably 0.15%. When the yield strength is 945 MPa or more, the lower limit of the V content is preferably 0.01%.
[0051] The chemical composition of the steel material described above may further contain one or more elements selected from the group consisting of Cu and Ni in place of a portion of Fe. All of these elements are optional elements and improve the hardenability of the steel material.
[0052] Cu: 0-0.50% Copper (Cu) is an optional element and may not be contained. That is, the Cu content may be 0%. When contained, Cu enhances the hardenability of the steel material and enhances the strength of the steel material. If even a small amount of Cu is contained, the above effect can be obtained to some extent. However, if the Cu content is too high, even if the contents of other elements are within the range of this embodiment, the hardenability of the steel material becomes too high, and the low-temperature toughness of the steel material decreases. Therefore, the Cu content is 0 to 0.50%. The preferred lower limit of the Cu content is more than 0%, more preferably 0.01%, more preferably 0.02%, and more preferably 0.03%. The preferred upper limit of the Cu content is 0.35%, more preferably 0.25%, more preferably 0.15%, more preferably 0.10%, and more preferably 0.05%.
[0053] Ni: 0 to 0.50% Nickel (Ni) is an optional element and may not be contained. That is, the Ni content may be 0%. When contained, Ni improves the hardenability of the steel material and increases the strength of the steel material. Ni also dissolves in the steel material to improve the low-temperature toughness of the steel material. Even if even a small amount of Ni is contained, these effects can be obtained to a certain extent. However, if the Ni content is too high, local corrosion is promoted and the low-temperature toughness of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Ni content is 0 to 0.50%. The preferred lower limit of the Ni content is more than 0%, more preferably 0.01%, and more preferably 0.02%. The preferred upper limit of the Ni content is 0.30%, more preferably 0.20%, more preferably 0.10%, and more preferably 0.05%.
[0054] The chemical composition of the above-mentioned steel material may further contain W instead of a portion of Fe.
[0055] W: 0~0.50% Tungsten (W) is an optional element and may not be contained. That is, the W content may be 0%. When W is contained, W forms a protective corrosion film in a sour environment and suppresses the penetration of hydrogen into the steel material. This increases the low-temperature toughness of the steel material. If even a small amount of W is contained, the above effect can be obtained to a certain extent. However, if the W content is too high, even if the contents of other elements are within the range of this embodiment, coarse carbides are generated in the steel material, and the low-temperature toughness of the steel material decreases. Therefore, the W content is 0 to 0.50%. The preferred lower limit of the W content is more than 0%, more preferably 0.01%, more preferably 0.03%, and more preferably 0.05%. The preferred upper limit of the W content is less than 0.50%, and more preferably 0.48%.
[0056] The chemical composition of the steel material described above may further contain, instead of a part of Fe, one or more elements selected from the group consisting of Ca, Mg, Zr, and rare earth elements. All of these elements are optional elements, and render S in the steel material harmless as sulfides. As a result, these elements increase the low-temperature toughness of the steel material.
[0057] Ca: 0 to 0.0100% Calcium (Ca) is an optional element and may not be contained. That is, the Ca content may be 0%. When contained, Ca renders S in the steel harmless as sulfides and increases the low-temperature toughness of the steel. If even a small amount of Ca is contained, the above effect can be obtained to some extent. However, if the Ca content is too high, even if the contents of other elements are within the range of this embodiment, the oxides in the steel will coarsen and the low-temperature toughness of the steel will decrease. Therefore, the Ca content is 0 to 0.0100%. The preferred lower limit of the Ca content is more than 0%, more preferably 0.0001%, more preferably 0.0003%, and more preferably 0.0006%. The preferred upper limit of the Ca content is 0.0040%, more preferably 0.0025%, more preferably 0.0020%, and more preferably 0.0015%.
[0058] Magnesium: 0 to 0.0100% Magnesium (Mg) is an optional element and may not be contained. That is, the Mg content may be 0%. When contained, Mg renders S in the steel harmless as sulfide, and increases the low-temperature toughness of the steel. If even a small amount of Mg is contained, the above effect can be obtained to some extent. However, if the Mg content is too high, even if the contents of other elements are within the range of this embodiment, the oxides in the steel will coarsen, and the low-temperature toughness of the steel will decrease. Therefore, the Mg content is 0 to 0.0100%. The preferable lower limit of the Mg content is more than 0%, more preferably 0.0001%, more preferably 0.0003%, and more preferably 0.0006%. The preferable upper limit of the Mg content is 0.0040%, more preferably 0.0025%, more preferably 0.0020%, and more preferably 0.0015%.
[0059] Zr: 0 to 0.0100% Zirconium (Zr) is an optional element and may not be contained. That is, the Zr content may be 0%. When contained, Zr renders S in the steel harmless as sulfide, and improves the low-temperature toughness of the steel. If even a small amount of Zr is contained, the above effect can be obtained to some extent. However, if the Zr content is too high, even if the contents of other elements are within the range of this embodiment, the oxides in the steel will coarsen, and the low-temperature toughness of the steel will decrease. Therefore, the Zr content is 0 to 0.0100%. The preferable lower limit of the Zr content is more than 0%, more preferably 0.0001%, more preferably 0.0003%, and more preferably 0.0006%. The preferable upper limit of the Zr content is 0.0040%, more preferably 0.0025%, more preferably 0.0020%, more preferably 0.0015%, and more preferably 0.0010%.
[0060] Rare earth elements (REM): 0~0.0100% Rare earth elements (REM) are optional elements and may not be contained. That is, the REM content may be 0%. When contained, REM renders S in the steel harmless as sulfides, and enhances the low-temperature toughness of the steel. REM further binds to P in the steel and suppresses the segregation of P at the grain boundaries. Therefore, the decrease in low-temperature toughness of the steel caused by the segregation of P is suppressed. If even a small amount of REM is contained, the above effect can be obtained to some extent even if the contents of other elements are within the range of this embodiment. However, if the REM content is too high, the oxides in the steel will coarsen and the low-temperature toughness of the steel will decrease even if the contents of other elements are within the range of this embodiment. Therefore, the REM content is 0 to 0.0100%. The preferable lower limit of the REM content is more than 0%, more preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.0006%. The upper limit of the REM content is preferably 0.0040%, more preferably 0.0025%, still more preferably 0.0020%, and still more preferably 0.0015%.
[0061] In this specification, REM refers to one or more elements selected from the group consisting of scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and the lanthanides lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. In addition, in this specification, the REM content refers to the total content of these elements.
[0062] [Yield strength] The yield strength of the steel material according to this embodiment is 862 to 1034 MPa (125 to 150 ksi). When the yield strength is less than 862 to 945 MPa, the yield strength in this specification means the stress at 0.65% elongation (0.65% proof stress) obtained in a tensile test at room temperature (25 ° C.) in accordance with ASTM E8 / E8M (2021). When the yield strength is 945 to 1034 MPa, the yield strength in this specification means the stress at 0.7% total elongation (0.7% total elongation proof stress) obtained in a tensile test at room temperature (25 ° C.) in accordance with ASTM E8 / E8M (2021). The steel material according to this embodiment has the above-mentioned chemical composition and satisfies the number density of the coarse Al oxides and the number density of the coarse Si oxides described later, so that even if the yield strength is 862 to 1034 MPa, it has excellent low-temperature toughness.
[0063] The yield strength of the steel material according to this embodiment is determined by the following method. First, a round bar test piece is prepared from the steel material according to this embodiment. When the steel material is a steel plate, the round bar test piece is prepared from the center of the plate thickness. In this case, the axial direction of the round bar test piece is parallel to the rolling direction of the steel plate. When the steel material is a steel pipe, the round bar test piece is prepared from the center of the wall thickness. In this case, the axial direction of the round bar test piece is parallel to the axial direction of the steel pipe. When the steel material is a round steel bar, the round bar test piece is prepared from the R / 2 position. In this specification, the R / 2 position means the center position of the radius R in a cross section perpendicular to the axial direction of the round steel bar. In this case, the axial direction of the round bar test piece is parallel to the axial direction of the round steel bar. The size of the round bar test piece is, for example, 8.9 mm in parallel part diameter and 35.6 mm in gauge length.
[0064] Using the prepared round bar test piece, a tensile test is performed at room temperature (25 ° C) in air in accordance with a method conforming to ASTM E8 / E8M (2021). If the obtained stress at 0.65% elongation (0.65% yield strength) is less than 862 to 945 MPa, the 0.65% yield strength is defined as the yield strength (MPa). If the obtained stress at 0.7% total elongation (0.7% total elongation yield strength) is 945 to 1034 MPa, the 0.7% total elongation yield strength is defined as the yield strength (MPa). In this embodiment, the yield strength (MPa) is obtained by rounding off the obtained value to the first decimal place.
[0065] [Number density of coarse Al oxide particles] The steel material according to the present embodiment has the above-mentioned chemical composition and a yield strength of 862 to 1034 MPa, and further has a number density of coarse Al oxides of 30 pieces / 200 mm 2 As described above, in this specification, particles having an Al content of 20% or more and an O content of 10% or more, in mass%, are also referred to as "Al oxides". As described above, in this specification, Al oxides having a major axis of 5.0 μm or more are also referred to as "coarse Al oxides". In other words, coarse Al oxides refer to particles having an Al content of 20% or more, an O content of 10% or more, and a major axis of 5.0 μm or more, in mass%.
[0066] As described above, when manufacturing a steel material having the above-mentioned chemical composition, deoxidation is mainly performed with aluminum (Al) in the steelmaking process. Therefore, a large amount of Al oxides is likely to be formed in the steel material having the above-mentioned chemical composition. Furthermore, Al oxides are hard oxides and are likely to reduce the toughness of the steel material. In particular, when the steel material has a high yield strength of 125 ksi or more, the effect of coarse Al oxides is likely to become apparent, and the low-temperature toughness is likely to decrease significantly. Therefore, in the steel material according to this embodiment having the above-mentioned chemical composition and a yield strength of 862 to 1034 MPa, the number density of coarse Al oxides is set to 30 particles / 200 mm 2 Less than.
[0067] In this embodiment, the preferred upper limit of the number density of the coarse Al oxide particles is 28 particles / 200 mm. 2 and more preferably 26 pieces / 200 mm 2 and more preferably 25 pieces / 200 mm 2 More preferably, 22 pieces / 200 mm 2 In this embodiment, the lower limit of the number density of the coarse Al oxides is not particularly limited, and is 0 particles / 200 mm 2 The lower limit of the number density of the coarse Al oxides may be, for example, 5 pieces / 200 mm 2 It may be 7 pieces / 200mm 2 Can be 9 pieces / 200mm 2The method for determining the number density of the coarse Al oxide particles will be described later.
[0068] [Number density of coarse Si oxides] The steel material according to the present embodiment has the above-mentioned chemical composition, a yield strength of 862 to 1034 MPa, and a number density of coarse Al oxides of 30 / 200 mm 2 The density of the coarse Si oxide particles is less than 5 particles / 200 mm. 2 As described above, in this specification, particles having an Al content of less than 20%, a Si content of 20% or more, and an O content of 10% or more, in mass%, are also referred to as "Si oxides". As described above, in this specification, Si oxides having a major axis of 5.0 μm or more are also referred to as "coarse Si oxides". In other words, coarse Si oxides refer to particles having an Al content of less than 20%, a Si content of 20% or more, an O content of 10% or more, and a major axis of 5.0 μm or more, in mass%,.
[0069] As mentioned above, silicon oxides have not received much attention because of their small number. However, when the steel has a high yield strength of 125 ksi or more, not only coarse aluminum oxides but also coarse silicon oxides in small numbers may easily cause a decrease in low-temperature toughness. Therefore, the number density of coarse aluminum oxides is set to 30 / 200 mm 2 Not only to reduce the number density of coarse silicon oxide particles to less than 5 particles / 200 mm 2 By setting the yield strength to 125 ksi or more, it is possible to stably obtain excellent low-temperature toughness. Therefore, the steel material according to the present embodiment has the above-mentioned chemical composition and a yield strength of 862 to 1034 MPa, and the number density of coarse Al oxides in the steel material is 30 particles / 200 mm 2 The density of the coarse Si oxide particles is less than 5 particles / 200 mm. 2 The following applies.
[0070] In this embodiment, the preferred upper limit of the density of the coarse Si oxide particles is 4 particles / 200 mm. 2 and more preferably 3 pieces / 200 mm 2In this embodiment, the lower limit of the number density of the coarse Si oxides is not particularly limited, and is 0 pieces / 200 mm 2 The lower limit of the density of the coarse Si oxide particles may be, for example, 1 particle / 200 mm. 2 may be also possible.
[0071] In this embodiment, the number density of coarse Al oxides and the number density of coarse Si oxides in the steel material can be obtained by the following method. First, a test piece is prepared from the steel material according to this embodiment, with the surface including the rolling direction and the rolling down direction as the observation surface. Specifically, when the steel material is a steel plate, a test piece is prepared from the center of the plate thickness, with the surface including the rolling direction and the plate thickness direction as the observation surface. When the steel material is a steel pipe, a test piece is prepared from the center of the plate thickness, with the surface including the pipe axial direction and the pipe radial direction as the observation surface. When the steel material is a round bar, a test piece is prepared with the R / 2 position in the center and the surface including the axial direction and the radial direction as the observation surface.
[0072] The observation surface of the prepared test piece is polished to a mirror finish before measurement. The area of the observation surface is not limited, but for example, 300 mm 2 (20mm x 15mm). On the observation surface, the number of Al oxides with a major axis of 5.0μm or more is counted. Furthermore, on the observation surface, the number of Si oxides with a major axis of 5.0μm or more is counted. Specifically, first, the particles on the observation surface are identified from the contrast. Each identified particle is subjected to element concentration analysis (EDS analysis). In the EDS analysis, the acceleration voltage is set to 20kV, and the target elements are quantified as N, O, Mg, Al, Si, P, S, Ca, Ti, Cr, Mn, Fe, Cu, Zr, and Nb. Based on the EDS analysis results of each particle, if the Al content is 20% or more by mass% and the O content is 10% or more, the particle is identified as "Al oxide". Based on the EDS analysis results of each particle, if the Al content is less than 20% by mass, the Si content is 20% or more, and the O content is 10% or more, the particle is identified as "Si oxide".
[0073] Among the Al oxides identified on the observation surface, Al oxides (coarse Al oxides) with a major axis of 5.0 μm or more are identified, and the total number of coarse Al oxides is calculated. Furthermore, among the Si oxides identified on the observation surface, Si oxides (coarse Si oxides) with a major axis of 5.0 μm or more are identified, and the total number of coarse Si oxides is calculated. The major axes of Al oxides and Si oxides can be calculated by a known method. In this specification, the major axis of Al oxides and Si oxides means the longest line segment among the line segments connecting any two points on the periphery of Al oxides and Si oxides on the observation surface.
[0074] Based on the total number of coarse Al oxides and the total area of the observation surface, the number density of the coarse Al oxides (pieces / 200 mm 2 Furthermore, the number density of the coarse Si oxides (pieces / 200 mm2) was calculated based on the total number of the coarse Si oxides and the total area of the observation surface. 2 In this embodiment, the number density (pieces / 200 mm 2 ), and the number density of coarse Si oxides (pieces / 200 mm 2 ) are all calculated by rounding off the obtained numerical value to the nearest tenth. The number density of the coarse Al oxides and the coarse Si oxides can be measured using a scanning electron microscope equipped with a composition analysis function (SEM-EDS device). For example, an automatic analyzer manufactured by FEI (ASPEX) under the trade name Metals Quality Analyzer can be used as the SEM-EDS device.
[0075] [Low temperature toughness] The steel material according to the present embodiment has the above-mentioned chemical composition, a yield strength of 862 to 1034 MPa, and a number density of coarse Al oxides of 30 / 200 mm 2 The density of the coarse Si oxide particles is less than 5 particles / 200 mm. 2 As a result, the steel material according to this embodiment has excellent low-temperature toughness even if the yield strength is 125 ksi or more. In this embodiment, having excellent low-temperature toughness is determined by a Charpy impact test in accordance with ASTM E23 (2018) described below.
[0076] First, a full-size or sub-size V-notch test piece is prepared from the steel material according to this embodiment in accordance with API 5CT (2019). Here, when the steel material is a steel plate, the rolling direction of the steel plate is defined as the "L direction" (Longitudinal), and the plate width direction of the steel plate is defined as the "T direction" (Transverse). When the steel material is a steel pipe, the pipe diameter direction of the steel pipe is defined as the "C direction", the pipe axial direction of the steel pipe is defined as the "L direction", and the direction perpendicular to the C direction and the L direction is defined as the "T direction". When the steel material is a round steel, the cross-sectional diameter direction of the round steel is defined as the "C direction", the axial direction of the round steel is defined as the "L direction", and the direction perpendicular to the C direction and the L direction is defined as the "T direction".
[0077] The prepared V-notch test specimen is subjected to a Charpy impact test in accordance with ASTM E23 (2018). Specifically, the test temperature is set to eight levels (-120°C, -100°C, -80°C, -60°C, -40°C, -20°C, 0°C, and 20°C) in which the test temperature is changed by 20°C in the range of -120 to 20°C. The Charpy impact test is performed using two test specimens for each test temperature. Under the above conditions, the brittle fracture rate (%) of the test specimen after the test at each temperature is obtained. The test temperature (°C) and the obtained brittle fracture rate (%) are plotted to obtain an approximation curve. From the obtained approximation curve, the temperature (°C) at which the brittle fracture rate becomes 50% is obtained and defined as the fracture transition temperature (°C). In this embodiment, the fracture transition temperature (°C) is obtained by rounding the obtained value to one decimal place.
[0078] In this embodiment, "excellent low-temperature toughness" is defined according to the range of yield strength. Specifically, when the yield strength is less than 862 to 945 MPa and the fracture appearance transition temperature is -50°C or lower, it is determined that the material has excellent low-temperature toughness. Also, when the yield strength is 945 to 1034 MPa and the fracture appearance transition temperature is -40°C or lower, it is determined that the material has excellent low-temperature toughness.
[0079] [Microstructure] The microstructure of the steel material according to this embodiment has a total volume fraction of tempered martensite and tempered bainite of 90% or more. The remainder of the microstructure is, for example, ferrite or pearlite. If the microstructure of the steel material having the above-mentioned chemical composition contains a total volume fraction of tempered martensite and tempered bainite of 90% or more, it can achieve both a yield strength of 125 ksi or more and excellent low-temperature toughness, provided that other configurations of this embodiment are satisfied. That is, in this embodiment, if the steel material achieves both a yield strength of 125 ksi or more and excellent low-temperature toughness, it is determined that the microstructure has a total volume fraction of tempered martensite and tempered bainite of 90% or more.
[0080] When the volume fractions of tempered martensite and tempered bainite are determined by observation, they can be determined by the following method. First, a test piece having an observation surface is prepared from the steel material according to this embodiment. When the steel material is a steel plate, a test piece is prepared from the center of the plate thickness, with a surface including the rolling direction and the plate thickness direction as the observation surface. When the steel material is a steel pipe, a test piece is prepared from the center of the plate thickness, with a surface including the pipe axial direction and the pipe radial direction as the observation surface. When the steel material is a round bar, a test piece is prepared that includes the R / 2 position in the center and has a surface including the axial direction and the radial direction as the observation surface.
[0081] The observation surface of the test piece is polished to a mirror finish, and then immersed in a nital etching solution for about 10 seconds to reveal the structure by etching. The etched observation surface is observed in 10 fields of view using a scanning electron microscope (SEM) in secondary electron images. The field area is, for example, 0.01 mm 2(magnification 1000x). In each field of view, tempered martensite and tempered bainite are identified from the contrast. The area ratios of the identified tempered martensite and tempered bainite are determined. The method for determining the area ratios is not particularly limited, and any known method may be used. For example, the area ratios of tempered martensite and tempered bainite can be determined by image analysis. In this embodiment, the arithmetic average value of the area ratios of tempered martensite and tempered bainite determined in all fields of view is defined as the volume ratios of tempered martensite and tempered bainite.
[0082] [Manufacturing method] A method for manufacturing a steel material according to this embodiment will be described below. A method for manufacturing a seamless steel pipe will be described below as an example of a steel material according to this embodiment. The method for manufacturing a seamless steel pipe includes a process for preparing a material (steelmaking process), a process for hot working the material to manufacture a mother pipe (hot working process), and a process for quenching and tempering the mother pipe to produce a seamless steel pipe (quenching process and tempering process). Note that the manufacturing method according to this embodiment is not limited to the manufacturing method described below. Each process will be described in detail below.
[0083] [Steel manufacturing process] In the steelmaking process, first, molten pig iron produced by a known method is refined in a converter (primary refining). The molten steel produced by the primary refining is then subjected to secondary refining. In the secondary refining, alloy elements are added to adjust the composition, and molten steel satisfying the above-mentioned chemical composition is produced.
[0084] In the secondary refining, for example, a Ruhrstahl-Hausen (RH) vacuum degassing treatment is performed. Then, the alloy components are finally adjusted. In the secondary refining, a composite refining may be performed. In this case, a refining treatment using, for example, a Ladle Furnace (LF) or a Vacuum Arc Degassing (VAD) is performed before the RH vacuum degassing treatment.
[0085] A material is manufactured using the molten steel that has been subjected to secondary refinement. Specifically, a cast piece (slab, bloom, or billet) is manufactured by continuous casting using the molten steel that has been subjected to secondary refinement. In the continuous casting method, first, the molten steel is poured from a ladle into a tundish. At this time, packing sand is usually enclosed in the nozzle of the ladle to seal the nozzle. Therefore, packing sand may be mixed with the molten steel from the ladle into the tundish. Also, when manufacturing a material having the above-mentioned chemical composition, silicon oxide may be used as the packing sand. In this case, there is a concern that silicon oxide may be introduced into the manufactured material.
[0086] Therefore, in this embodiment, in order to prevent the Si oxide sealed in the nozzle of the ladle from being introduced into the tundish, the molten steel and the Si oxide are separated. The method of separating the Si oxide is not particularly limited, but the following method can be used, for example. A metal plate with an inclination is placed below the nozzle of the ladle and above the opening of the tundish. When the nozzle of the ladle is opened, the Si oxide is discharged from the nozzle first, and then the molten steel is discharged. Here, the Si oxide is lighter than the molten steel. Therefore, the Si oxide discharged from the nozzle is guided to the outside of the opening of the tundish along the inclination of the metal plate. The inclination of the metal plate may be provided, for example, by disposing a metal plate processed into a cone shape without a bottom surface so that the apex is located directly below the nozzle of the ladle, or may be provided by other methods. In addition, one metal plate may be used, or multiple metal plates may be used in a stacked manner. Furthermore, the thickness of the metal plate is not particularly limited, but is, for example, about 1 to 10 mm.
[0087] After the Si oxide is discharged from the nozzle, the molten steel is discharged. At this time, the molten steel discharged from the nozzle is introduced into the tundish through the opening together with the metal plate. That is, in this embodiment, a part or all of the metal plate may be introduced into the tundish and mixed into the molten steel. Therefore, the metal plate in this embodiment is preferably a metal plate made of alloy elements contained in the molten steel. As the metal plate made of alloy elements contained in the molten steel, for example, an aluminum plate can be used. In this specification, the aluminum plate means a metal plate made of aluminum and the balance of impurities.
[0088] Preferably, after the Si oxide is discharged from the nozzle, the metal plate is removed from below the nozzle before the molten steel is discharged. In this case, it is possible to prevent the Si oxide attached to the metal plate from being mixed into the molten steel. The method for removing the metal plate from below the nozzle is not particularly limited, but for example, a hole may be formed in a part of the metal plate, and the metal plate may be removed using a rod with a hook at its tip. In this case, the hook at the tip of the rod can be hooked into the hole in the metal plate and the rod can be pulled to remove the metal plate. By the above method, the Si oxide can be separated from the molten steel and the molten steel can be introduced into the tundish. The method for separating the Si oxide from the molten steel is not limited to the above method.
[0089] Next, the prepared molten steel is cast to produce a material. The casting method is not particularly limited, but may be, for example, a continuous casting method. When producing a material by a continuous casting method, it is preferable to carry out the following method.
[0090] The casting speed in the continuous casting machine is preferably 1.0 to 3.0 m / min. If the casting speed is too slow, an accumulation zone of Al oxides may be formed in the material. In this case, the produced steel material contains a large amount of coarse Al oxides, and the low-temperature toughness of the steel material decreases. On the other hand, if the casting speed is too fast, the Al oxides may not float up, and a large amount of Al oxides may remain in the material. In this case, the produced steel material contains a large amount of coarse Al oxides, and the low-temperature toughness of the steel material decreases. Therefore, the casting speed in the continuous casting machine is preferably 1.0 to 3.0 m / min.
[0091] When the material is manufactured by the continuous casting method, it is preferable to further electromagnetically stir the molten steel in the mold. Specifically, by performing the electromagnetic stirring in the mold with a current value of 330 to 450A, it becomes difficult for an accumulation zone of Al oxide to be formed in the material. If the current value of the electromagnetic stirring in the mold is too low, the stirring of the molten steel is insufficient, and an accumulation zone of Al oxide may be formed in the material. In this case, a large number of coarse Al oxides are contained in the manufactured steel material, and the low-temperature toughness of the steel material decreases. On the other hand, if the current value of the electromagnetic stirring in the mold is too high, the manufacturing equipment may be overloaded. Therefore, in this embodiment, it is preferable to set the current value of the electromagnetic stirring in the mold to 330 to 450A. By the above method, the molten steel is cast to manufacture the material.
[0092] [Hot processing process] In the hot working process, the prepared material is hot worked to produce an intermediate steel material. When the steel material is a seamless steel pipe, the intermediate steel material corresponds to a mother pipe. First, the billet is heated in a heating furnace. The heating temperature is not particularly limited, but is, for example, 1100 to 1300°C. The billet extracted from the heating furnace is hot worked to produce a mother pipe (seamless steel pipe). The method of hot working is not particularly limited, and may be a well-known method.
[0093] For example, the Mannesmann process may be carried out as the hot working to produce a mother pipe. In this case, a round billet is pierced and rolled using a piercing machine. When piercing and rolling is performed, the piercing ratio is not particularly limited, but is, for example, 1.0 to 4.0. The pierced and rolled round billet is further hot rolled using a mandrel mill, a reducer, a sizing mill, or the like to produce a mother pipe. The cumulative reduction in area in the hot working process is, for example, 20 to 70%.
[0094] Other hot working methods may be used to produce a mother pipe from the billet. For example, in the case of a short, thick-walled steel material such as a coupling, the mother pipe may be produced by forging using the Erhardt method or the like. The mother pipe is produced by the above steps. The thickness of the mother pipe is not particularly limited, but is, for example, 9 to 60 mm.
[0095] When the steel material is round steel, the material is first heated in a heating furnace. The heating temperature is not particularly limited, but is, for example, 1100 to 1300°C. The material extracted from the heating furnace is subjected to hot processing to produce an intermediate steel material having a circular cross section perpendicular to the axial direction. The hot processing is, for example, blooming rolling by a blooming mill, or hot rolling by a continuous rolling mill. In the continuous rolling mill, a horizontal stand having a pair of grooved rolls arranged side by side in the vertical direction and a vertical stand having a pair of grooved rolls arranged side by side in the horizontal direction are alternately arranged.
[0096] When the steel material is a steel plate, the material is first heated in a heating furnace. The heating temperature is not particularly limited, but is, for example, 1100 to 1300° C. The material removed from the heating furnace is subjected to hot rolling using a blooming mill and a continuous rolling mill to produce an intermediate steel material in the shape of a steel plate.
[0097] The mother pipe produced by hot working may be air-cooled (as-rolled). The mother pipe produced by hot working may be quenched directly after the hot working without being cooled to room temperature, or may be quenched after being reheated after the hot working.
[0098] When quenching is performed directly after hot working, or after reheating, cooling may be stopped or slow cooling may be performed during quenching. In this case, it is possible to prevent quench cracks from occurring in the mother pipe. When quenching is performed directly after hot working, or after reheating, stress relief annealing (SR) may be performed after quenching and before the next heat treatment. In this case, residual stress in the mother pipe is removed.
[0099] As described above, in the hot working process, the prepared material is hot worked to produce an intermediate steel material. The quenching process will be described in detail below.
[0100] [Quenching process] In the quenching process, quenching is performed on the prepared intermediate steel material (blank pipe). In this specification, "quenching" means rapidly cooling the intermediate steel material at the A3 point or higher. The quenching temperature is preferably 800 to 1000°C. If the quenching temperature is too high, the prior γ grains may become coarse, and the low-temperature toughness of the steel material may decrease. Therefore, the quenching temperature is preferably 800 to 1000°C.
[0101] In this specification, the quenching temperature corresponds to the surface temperature of the intermediate steel material measured by a thermometer installed at the outlet side of the device performing the final hot working when quenching is performed directly after hot working. Furthermore, the quenching temperature corresponds to the temperature of the furnace where quenching or reheating is performed when quenching is performed after reheating or reheating after hot working.
[0102] The quenching method is, for example, to continuously cool the intermediate steel material (mother pipe) from the quenching start temperature to continuously lower the surface temperature of the mother pipe. The method of continuous cooling is not particularly limited and may be a well-known method. For example, the method of continuous cooling is a method of immersing the mother pipe in a water tank for cooling, or a method of accelerating cooling the mother pipe by shower water cooling or mist cooling.
[0103] If the cooling rate during quenching is too slow, the microstructure will not be mainly martensite and bainite, and the mechanical properties (yield strength of 862 to 1034 MPa) specified in this embodiment will not be obtained, and in this case, excellent low-temperature toughness will not be obtained.
[0104] Therefore, as described above, in the steel manufacturing method according to the present embodiment, the intermediate steel is quenched during quenching. Specifically, in the quenching step, the average cooling rate in the range of the surface temperature of the intermediate steel (blank pipe) during quenching from 800 to 500°C is defined as the quenching cooling rate CR. 800-500 More specifically, the cooling rate during quenching, CR 800-500 is determined from the temperature measured at the slowest cooling location in the cross section of the intermediate steel being quenched (e.g., the center of the intermediate steel thickness when both surfaces are forced cooled).
[0105] Preferred cooling rate during quenching: CR 800-500 The cooling rate during quenching is preferably 300°C / min or more. 800-500 The lower limit of the cooling rate during quenching is 450° C. / min, and more preferably 600° C. / min. 800-500 The upper limit is not particularly specified, but is, for example, 60,000° C. / min.
[0106] Preferably, the mother tube is heated in the austenite region multiple times and then quenched. In this case, the austenite grains before quenching are refined, thereby improving the low-temperature toughness of the steel material. By performing quenching multiple times, heating in the austenite region may be repeated multiple times, or by performing normalizing and quenching, heating in the austenite region may be repeated multiple times. Furthermore, quenching and tempering, which will be described later, may be combined and performed multiple times. That is, quenching and tempering may be performed multiple times. In this case, the low-temperature toughness of the steel material is further improved. The tempering process will be described in detail below.
[0107] [Tempering process] In the tempering process, the above-mentioned quenched blank pipe is tempered. In this specification, "tempering" refers to the process of tempering the intermediate steel material after quenching to A c1 The term "tempering temperature" refers to the temperature of a furnace in which the intermediate steel material is heated and held after quenching at a temperature lower than the tempering temperature. The term "tempering time" refers to the time from when the temperature of the intermediate steel material reaches a predetermined tempering temperature until it is extracted from the heat treatment furnace.
[0108] The tempering temperature is appropriately adjusted according to the chemical composition of the seamless steel pipe and the yield strength to be obtained. That is, the tempering temperature is adjusted for a mother pipe having the chemical composition of this embodiment to adjust the yield strength of the seamless steel pipe to 862 to 1034 MPa. It is naturally possible for a person skilled in the art to adjust the tempering temperature to adjust the yield strength of the seamless steel pipe to 862 to 1034 MPa. Specifically, in the tempering process according to this embodiment, the preferred tempering temperature is 580 to 690°C.
[0109] If the tempering time is too short, a microstructure mainly composed of tempered martensite and tempered bainite may not be obtained. On the other hand, if the tempering time is too long, the above effects are saturated. Therefore, in the tempering step of this embodiment, the tempering time is preferably 10 to 90 minutes. A more preferable lower limit of the tempering time is 15 minutes. A more preferable upper limit of the tempering time is 80 minutes.
[0110] The steel material according to this embodiment can be manufactured by the above manufacturing method. In the above manufacturing method, a method for manufacturing a seamless steel pipe has been described as one example. However, the steel material according to this embodiment may be a steel plate or other shape. Similar to the above manufacturing method, the manufacturing method for steel plate or other shape also includes, for example, a preparation step, a quenching step, and a tempering step. Furthermore, the above manufacturing method is one example, and the steel material may be manufactured by other manufacturing methods.
[0111] The present invention will now be described in more detail with reference to examples. EXAMPLES
[0112] In Example 1, steel materials having a yield strength of 862 to less than 945 MPa were investigated. Specifically, molten steels having the chemical compositions shown in Tables 1-1 and 1-2 were produced. In Table 1-2, "-" means that the content of each element is at the impurity level. Specifically, the V content, Cu content, Ni content, and W content of Steel A were 0% after rounding off to the nearest two decimal places. Furthermore, the Ca content, Mg content, Zr content, and rare earth element (REM) content of Steel A were 0% after rounding off to the nearest five decimal places.
[0113] [Table 1-1]
[0114] [Table 1-2]
[0115] Using the above molten steel, a round billet was manufactured by a continuous casting method. In the continuous casting method, when pouring molten steel from a ladle into a tundish, a metal plate processed into a bottomless cone shape was placed above the opening of the tundish so that its apex was located directly below the nozzle of the ladle. Table 2 shows whether or not a metal plate of the above shape was placed above the opening of the tundish. Specifically, when a metal plate of the above shape was placed above the opening of the tundish, "A" is indicated in the "Metal Plate" column of Table 2. When a metal plate of the above shape was not placed above the opening of the tundish, "B" is indicated in the "Metal Plate" column of Table 2. The metal plate of the above shape placed above the opening of the tundish was an aluminum plate. Specifically, three aluminum plates with a thickness of 2 mm were used in a stack. In addition, when a metal plate was placed, after the Si oxide was discharged from the nozzle and before the molten steel was discharged, the metal plate was removed from below the nozzle using a rod with a hook formed at the tip. Furthermore, the molten steel was cast into a round billet at the casting speed shown in Table 2. At this time, electromagnetic stirring was performed in the mold at the current value shown in Table 2.
[0116] [Table 2]
[0117] The manufactured round billets of test numbers 1 to 20 were held at 1250°C for 1 hour, and then hot rolling was performed by the Mannesmann-mandrel method to manufacture mother pipes (seamless steel pipes) of test numbers 1 to 20. Furthermore, the obtained mother pipes of test numbers 1 to 20 were quenched. Specifically, the mother pipes of test numbers 1 to 20 were held at the temperature (°C) for the time (minutes) listed in the "Quenching process" column in Table 2, and then quenched by shower water cooling. Note that in test numbers 1 to 20, the cooling rate during quenching, CR 800-500 The quenching rates were all within the range of 480 to 30,000°C / min. The quenching temperatures (°C) shown in Table 2 were the temperatures (°C) of the heat treatment furnace in which the mother tube was heated. Furthermore, the quenching times (min) shown in Table 2 were the times (min) the mother tube was held at the quenching temperature.
[0118] The obtained mother pipes of test numbers 1 to 20 were tempered. Specifically, the mother pipes of test numbers 1 to 20 were tempered by holding them at the temperature (°C) for the time (minutes) listed in the "Tempering step" column of Table 2. Here, the tempering temperature (°C) listed in Table 2 is the temperature (°C) of the tempering furnace in which the mother pipes were heated. Furthermore, the tempering time (minutes) listed in Table 2 is the time (minutes) during which the mother pipes were held at the tempering temperature. Through the above manufacturing process, seamless steel pipes of test numbers 1 to 20 were obtained.
[0119] [Evaluation test] The seamless steel pipes of test numbers 1 to 20 after tempering were subjected to a tensile test, a measurement test of the number density of coarse Al oxides and coarse Si oxides, and a Charpy impact test, all of which will be described below.
[0120] [Tensile test] A tensile test was performed on the seamless steel pipes of test numbers 1 to 20 to determine the yield strength. The tensile test was performed in accordance with ASTM E8 / E8M (2021). Round bar test pieces with a parallel part diameter of 8.9 mm and a gauge length of 35.6 mm were prepared from the center of the wall thickness of the seamless steel pipes of test numbers 1 to 20. The axial direction of the round bar test pieces was parallel to the axial direction of the seamless steel pipes. Using the prepared round bar test pieces, a tensile test was performed at room temperature (25 ° C.) in air to obtain the yield strength (MPa) of the seamless steel pipes of test numbers 1 to 20. In this embodiment, the stress at 0.65% elongation (0.65% proof stress) obtained in the tensile test was defined as the yield strength. The obtained yield strength (MPa) is shown in Table 3 as "YS (MPa)".
[0121] [Table 3]
[0122] [Measurement of the number and density of coarse Al oxides and coarse Si oxides] A number density measurement test of coarse Al oxides and coarse Si oxides was carried out on the seamless steel pipes of test numbers 1 to 20 to determine the number density of Al oxides (coarse Al oxides) with a major axis of 5.0 μm or more and Si oxides (coarse Si oxides) with a major axis of 5.0 μm or more. The number densities of coarse Al oxides and coarse Si oxides were determined by the above-mentioned method using test pieces prepared from the central part of the wall thickness of the seamless steel pipes of test numbers 1 to 20. The number densities of the coarse Al oxides (particles / 200 mm 2 ) in Table 3, "Coarse Al oxide (pieces / 200 mm 2 The number density (pieces / 200 mm) of the obtained coarse Si oxides is shown in the column. 2 ) in Table 3, "Large Si oxide (pieces / 200 mm 2 ) column.
[0123] [Charpy impact test] A Charpy impact test was performed on the seamless steel pipes of test numbers 1 to 20 to evaluate the low temperature toughness. A full-sized V-notch test piece was prepared from the center of the wall thickness of the seamless steel pipes of test numbers 1 to 20. The longitudinal direction of the test piece was parallel to the circumferential direction of the pipe. The circumferential direction of the pipe means a direction perpendicular to both the axial direction and the radial direction of the seamless steel pipe. The notch surface of the test piece was perpendicular to the axial direction of the seamless steel pipe. A Charpy impact test was performed under the above conditions in accordance with ASTM E23 (2018) to obtain the brittle fracture rate (%) of test numbers 1 to 20. The temperature (℃) at which the brittle fracture rate became 50% was obtained from the approximation curve of the plot of the test temperature (℃) and the brittle fracture rate (%), and was taken as the fracture transition temperature (℃). The obtained fracture transition temperatures (℃) are shown in Table 3.
[0124] [Evaluation Results] With reference to Tables 1-1, 1-2, 2, and 3, the seamless steel pipes of test numbers 1 to 12 had appropriate chemical compositions, and the manufacturing methods also satisfied the above-mentioned preferable conditions. As a result, the seamless steel pipes had a yield strength of 862 to less than 945 MPa and a number density of coarse Al oxides of 30 particles / 200 mm 2 The density of the coarse Si oxide particles is less than 5 particles / 200 mm. 2 As a result, the seamless steel pipes had a fracture appearance transition temperature of -50°C or less in the Charpy impact test. That is, the seamless steel pipes of test numbers 1 to 12 had a yield strength of 862 to less than 945 MPa and excellent low-temperature toughness. It was determined that the total volume fraction of tempered martensite and tempered bainite in the microstructure of these seamless steel pipes was 90% or more.
[0125] On the other hand, the seamless steel pipes of test numbers 13 and 14 were cast at too high a speed in the steelmaking process. As a result, the number density of coarse Al oxides in these seamless steel pipes was 30 pieces / 200 mm 2 As a result, the fracture appearance transition temperature of these seamless steel pipes exceeded -50°C in the Charpy impact test, and they did not have excellent low-temperature toughness.
[0126] For the seamless steel pipes of test numbers 15 to 17, no metal plate was used in the steelmaking process. As a result, the number density of coarse Si oxides in these seamless steel pipes was 5 pieces / 200 mm 2 As a result, the fracture appearance transition temperature of these seamless steel pipes exceeded -50°C in the Charpy impact test, and they did not have excellent low-temperature toughness.
[0127] The seamless steel pipe of test number 18 had an excessively high O content. As a result, the fracture appearance transition temperature of this seamless steel pipe exceeded -50°C in the Charpy impact test, and the seamless steel pipe did not have excellent low-temperature toughness.
[0128] The seamless steel pipe of test number 19 had an excessively low Mo content, and as a result, the fracture transition temperature of this seamless steel pipe exceeded -50°C in the Charpy impact test, and the seamless steel pipe did not have excellent low-temperature toughness.
[0129] The seamless steel pipe of test number 20 had an excessively high S content. As a result, the fracture transition temperature of this seamless steel pipe exceeded -50°C in the Charpy impact test, and the seamless steel pipe did not have excellent low-temperature toughness. EXAMPLES
[0130] In Example 2, steel materials with yield strengths of 945 to 1034 MPa were investigated. Specifically, molten steels having the chemical compositions shown in Tables 4-1 and 4-2 were produced. In Table 4-2, "-" means that the content of each element is at the impurity level. Specifically, the Cu content, Ni content, and W content of Steel A were 0% after rounding off to the nearest two decimal places. Furthermore, the Ca content, Mg content, Zr content, and rare earth element (REM) content of Steel A were 0% after rounding off to the nearest five decimal places.
[0131] [Table 4-1]
[0132] [Table 4-2]
[0133] As in Example 1, a round billet was produced by continuous casting using the above molten steel. In the continuous casting method, when pouring molten steel from a ladle into a tundish, a metal plate processed into a bottomless cone shape was placed above the opening of the tundish so that its apex was located directly below the nozzle of the ladle. Table 5 shows whether or not a metal plate of the above shape was placed above the opening of the tundish. Specifically, when a metal plate of the above shape was placed above the opening of the tundish, "A" is indicated in the "Metal Plate" column of Table 5. When a metal plate of the above shape was not placed above the opening of the tundish, "B" is indicated in the "Metal Plate" column of Table 5. The metal plate of the above shape placed above the opening of the tundish was an aluminum plate. Specifically, three aluminum plates with a thickness of 2 mm were used in a stack. In addition, when a metal plate was placed, after the Si oxide was discharged from the nozzle and before the molten steel was discharged, the metal plate was removed from below the nozzle using a rod with a hook formed at the tip. Further, the molten steel was cast into a round billet at the casting speed shown in Table 5. At this time, electromagnetic stirring was performed in the mold at the current value shown in Table 5.
[0134] [Table 5]
[0135] As in Example 1, the manufactured round billets of test numbers 21 to 38 were held at 1250°C for 1 hour, and then hot rolling was performed by the Mannesmann-mandrel method to manufacture mother pipes (seamless steel pipes) of test numbers 21 to 38. Furthermore, the obtained mother pipes of test numbers 21 to 38 were quenched. Specifically, the mother pipes of test numbers 21 to 38 were held at the temperature (°C) for the time (minutes) listed in the "Quenching process" column in Table 5, and then quenched by shower water cooling. Note that in test numbers 21 to 38, the cooling rate during quenching, CR 800-500The quenching rates were all within the range of 480 to 30,000°C / min. The quenching temperatures (°C) shown in Table 5 are the temperatures (°C) of the heat treatment furnace in which the mother tube was heated. Furthermore, the quenching times (min) shown in Table 5 are the times (min) the mother tube was held at the quenching temperature.
[0136] The obtained mother pipes of test numbers 21 to 38 were tempered in the same manner as in Example 1. Specifically, the mother pipes of test numbers 21 to 38 were tempered by holding them at the temperature (°C) for the time (minutes) listed in the "Tempering step" column of Table 5. Here, the tempering temperature (°C) listed in Table 5 is the temperature (°C) of the tempering furnace in which the mother pipe was heated. Furthermore, the tempering time (minutes) listed in Table 5 is the time (minutes) for which the mother pipe was held at the tempering temperature. Through the above manufacturing process, seamless steel pipes of test numbers 21 to 38 were obtained.
[0137] [Evaluation test] The seamless steel pipes of test numbers 21 to 38 after tempering were subjected to a tensile test, a measurement test of the number density of coarse Al oxides and coarse Si oxides, and a Charpy impact test, all of which will be described below.
[0138] [Tensile test] A tensile test was performed on the seamless steel pipes of test numbers 21 to 38 to determine the yield strength. The tensile test was performed in accordance with ASTM E8 / E8M (2021). Round bar test pieces with a parallel part diameter of 8.9 mm and a gauge length of 35.6 mm were prepared from the center of the wall thickness of the seamless steel pipes of test numbers 21 to 38. The axial direction of the round bar test pieces was parallel to the pipe axial direction of the seamless steel pipes. Using the prepared round bar test pieces, a tensile test was performed at room temperature (25 ° C.) in air to obtain the yield strength (MPa) of the seamless steel pipes of test numbers 21 to 38. In this embodiment, the stress at 0.7% total elongation obtained in the tensile test (0.7% total elongation yield strength) was defined as the yield strength. The obtained yield strength (MPa) is shown in Table 6 as "YS (MPa)".
[0139] [Table 6]
[0140] [Measurement of the number and density of coarse Al oxides and coarse Si oxides] A number density measurement test of coarse Al oxides and coarse Si oxides was carried out on the seamless steel pipes of test numbers 21 to 38 to determine the number density of Al oxides with a major axis of 5.0 μm or more (coarse Al oxides) and Si oxides with a major axis of 5.0 μm or more (coarse Si oxides). The number densities of coarse Al oxides and coarse Si oxides were determined by the above-mentioned method using test pieces prepared from the central part of the wall thickness of the seamless steel pipes of test numbers 21 to 38. The number densities of the coarse Al oxides (particles / 200 mm 2 ) in Table 6. 2 The number density (pieces / 200 mm) of the obtained coarse Si oxides is shown in the column. 2 ) in Table 6, "Large Si oxide (pieces / 200 mm 2 ) column.
[0141] [Charpy impact test] A Charpy impact test was performed on the seamless steel pipes of test numbers 21 to 38 to evaluate the low temperature toughness. Full-sized V-notch test pieces were prepared from the center of the wall thickness of the seamless steel pipes of test numbers 21 to 38. The longitudinal direction of the test piece was parallel to the circumferential direction of the pipe. The circumferential direction of the pipe means a direction perpendicular to both the axial direction and the radial direction of the seamless steel pipe. The notch surface of the test piece was perpendicular to the axial direction of the seamless steel pipe. A Charpy impact test was performed under the above conditions in accordance with ASTM E23 (2018) to obtain the brittle fracture rate (%) of test numbers 21 to 38. The temperature (℃) at which the brittle fracture rate becomes 50% was obtained from the approximation curve of the plot of the test temperature (℃) and the brittle fracture rate (%), and was taken as the fracture transition temperature (℃). The obtained fracture transition temperatures (℃) are shown in Table 6.
[0142] [Evaluation Results] With reference to Tables 4-1, 4-2, 5, and 6, the seamless steel pipes of test numbers 21 to 32 had appropriate chemical compositions, and the manufacturing methods also satisfied the above-mentioned preferable conditions. As a result, these seamless steel pipes had a yield strength of 945 to 1034 MPa and a number density of coarse Al oxides of 30 particles / 200 mm 2The density of the coarse Si oxide particles is less than 5 particles / 200 mm. 2 As a result, the seamless steel pipes had a fracture appearance transition temperature of -40°C or less in the Charpy impact test. That is, the seamless steel pipes of test numbers 21 to 32 had a yield strength of 945 to 1034 MPa and excellent low-temperature toughness. It was determined that the total volume fraction of tempered martensite and tempered bainite in the microstructure of these seamless steel pipes was 90% or more.
[0143] On the other hand, the seamless steel pipes of test numbers 33 and 34 were cast at too high a speed in the steelmaking process. As a result, the number density of coarse Al oxides in these seamless steel pipes was 30 pieces / 200 mm 2 As a result, these seamless steel pipes had fracture appearance transition temperatures exceeding -40°C in Charpy impact tests, and did not have excellent low-temperature toughness.
[0144] For the seamless steel pipes of test numbers 35 and 36, no metal plate was used in the steelmaking process. As a result, the number density of coarse Si oxides in these seamless steel pipes was 5 pieces / 200 mm 2 As a result, the fracture appearance transition temperature of these seamless steel pipes exceeded -40°C in the Charpy impact test, and they did not have excellent low-temperature toughness.
[0145] The seamless steel pipe of test number 37 had an excessively high O content. As a result, the fracture appearance transition temperature of this seamless steel pipe exceeded -40°C in the Charpy impact test, and the seamless steel pipe did not have excellent low-temperature toughness.
[0146] The seamless steel pipe of test number 38 had an excessively high S content. As a result, the fracture transition temperature of this seamless steel pipe exceeded -40°C in the Charpy impact test, and the seamless steel pipe did not have excellent low-temperature toughness.
[0147] The embodiments of the present disclosure have been described above. However, the above-described embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments, and can be implemented by appropriately modifying the above-described embodiments without departing from the spirit of the present disclosure.
Claims
1. A steel material, In mass percent, C: 0.15-0.45%, Si: 0.05-1.00%, Mn: 0.05-1.00%, P: 0.030% or less, S: 0.0050% or less, Al: 0.005-0.100%, Cr: 0.30-1.50%, Mo: 0.20-2.00%, Ti: 0.002 to 0.030%, Nb: 0.002-0.100%, B: 0.0005-0.0040%, N: 0.0100% or less, O: 0.0040% or less, V: 0 to 0.30%, Cu: 0 to 0.50%, Ni: 0 to 0.50%, W: 0-0.50%, Ca: 0-0.0100%, Mg: 0 to 0.0100%, Zr: 0 to 0.0100%, Rare earth elements: 0 to 0.0100%, and The balance is Fe and impurities, The yield strength is 862 to 1034 MPa; In the microstructure of the steel material, the total volume fraction of tempered martensite and tempered bainite is 90% or more, In the steel material, The Al content is 20% or more, the O content is 10% or more, and the number density of Al oxides having a major axis of 5.0 μm or more is 30 / 200 mm 2 is less than In the case where the Al content is less than 20%, the Si content is 20% or more, the O content is 10% or more, and the number density of Si oxides having a major axis of 5.0 μm or more is 5 pieces / 200 mm 2 Below is the Steel material.
2. The steel material according to claim 1, V: 0.01-0.30%, Cu: 0.01 to 0.50%, Ni: 0.01-0.50%, W: 0.01-0.50%, Ca: 0.0001-0.0100%, Mg: 0.0001 to 0.0100%, Zr: 0.0001 to 0.0100%, and Rare earth elements: containing one or more elements selected from the group consisting of 0.0001 to 0.0100%; Steel material.
3. The steel material according to claim 1 or 2, The steel material is a seamless steel pipe. Steel material.
Citation Information
Patent Citations
Continuous casting tundish
JP2003245756A
Continuous casting method
JP2008254051A
Steel suitable for use in sour environments
JP7406177B1
Low-alloy, high-strength seamless steel pipe for oil well
WO2017149571A1
High-strength seamless steel pipe for oil well and method for producing same
WO2018074109A1
Cited By
Steel material
JPWO2025033002A1
Steel material
JPWO2025033003A1